HOW DOES SCHOOL SOLVE LEARNING DIFFICULTIES IN THE VUCA ERA? - Rosyid, Dede Ar; Nur'Aini, Dina Alifta; Lestari, Chika Putri; Arifin, Syamsul; Nurjan, Syarifan (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
The big role of teachers is not only to convey knowledge, educate, direct, and teach attitudes of responsibility, but also to find solutions to learning difficulties that occur during the learning process. The current new era, namely VUCA, is a transition from traditional to digital systems that make all information can be obtained quickly. This era has both positive and negative impacts on students. Such as the negative impact that occurs on SMPIT Insan Madani students where some students experience learning difficulties which results in decreased learning outcomes. This research aims to help solve the problem of learning difficulties there. This research was carried out using literature review methods, interview methods, and direct observation. Researchers found interesting things in solving the learning difficulties of students at SMPIT Insan Madani in several special ways, namely: psychological approach, nature-based schooling, and constructivity approach. Researchers hope these results will continue to provide benefits in the future for readers, related schools or other schools that experience similar learning difficulties.